Determinants on job performance among expatriate in multinational companies / Nurizzati Jamaludin and Shazreen Amira Saiful Azhar - Jamaludin, Nurizzati; Saiful Azhar, Shazreen Amira (Faculty of Business and Management, 2014)
The purpose of this research is to study the level of employees’ job performances among expatriates in Malaysia. The researcher also wants to identify which factor to be the most significant factor that influences job performance among expatriates. Other than that, the researcher also wants to identify relationship between job performances and some of the determinants which are salary, working environment, and job security. This study refers to primary data and also secondary data for supporting the sampling technique. The researchers used questionnaire as the method to collect all the data from the sample respondents in accomplishing the research objectives. For the next stage, the data for this study was analyzed using multiple statistical procedures; frequencies and correlation analysis. The result of the study presented in this research agrees that good working environment have a significant relationship with employees’ job performance while salary and job security is on the way round. This study can be seen as a foreword to a more detailed study to be carrying by future research on the motivational practices.